In-Plane Oriented Two-Dimensional Conjugated Metal-Organic Framework Films for High-Performance Humidity Sensing - Park, Sang Wook; Zhang, Zhe; Qi, Haoyuan; Liang, Baokun; Mahmood, Javeed; Noh, Hyuk-Jun; Hambsch, Mike; Wang, Mingchao; Wang, Mao; Ly, Khoa Hoang; Wang, Zhiyong; Weidinger, Inez M.; et al. (ACS Materials Letters, 2022)
Two-dimensional conjugated metal-organic frameworks (2D c-MOFs) have emerged as a new generation of conducting MOFs for electronics. However, controlled synthesis of thin-film samples with high crystallinity and defined layer orientation, which is beneficial for achieving high-performance devices and reliable structure-property relationship, has remained a challenge. Here, we develop a surfactant-directed two-step synthesis of layered 2D c-MOF films based on benzene and triphenylene ligands linked by copper-bis(diimino) complexes (HIB-Cu and HITP-Cu, respectively). The achieved layered 2D c-MOF films are featured as free-standing, in-plane oriented, and polycrystalline films with domain size up to ∼8000 nm2and a tunable thickness in the range of 8-340 nm. Benefiting from the intrinsic electrical conductivity and quasi-one-dimensional pore channels, a HIB-Cu film based chemiresistive sensor is constructed, displaying effective humidity sensing with a response as fast as ∼21 s, superior to the reported MOF-powder-based chemiresistive sensors (in the orders of minutes).
CRIS-Team Scopus Importer:2023-03-20